Using Sephonics in Teaching Speaking To The first Grade of Junior High School Students - Amsa, Helfany; Burhan , Kristian; Efrina, Gusnita (Pustaka Galeri Mandiri, 2022)
Many students think that learning English is very difficult and boring. This is because English is a foreign language and they are afraid to make mistakes. This happens due to various factors, such as lack of mastery of vocabulary and grammar, improper pronunciation and a learning atmosphere that cannot attract students. These problems can be found in all aspects of ability in English, especially in speaking. Qualitative method used in this study and content analysis will ne used as data analysis. Based on the study, the writer conclude that English teachers in junior high schools, especially first graders, can also use Sephonics to improve students' English pronunciation, so that students will be more interested in learning, be active, and can also improve their language skills.